2021
DOI: 10.1002/alz.12321
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of neurofibrillary tangle maturity in Alzheimer's disease: A clinicopathologic perspective for biomarker research

Abstract: Neurofibrillary tangles, one of the neuropathologic hallmarks of Alzheimer's disease, have a dynamic lifespan of maturity that associates with progressive neuronal dysfunction and cognitive deficits. As neurofibrillary tangles mature, the biology of the neuron undergoes extensive changes that may impact biomarker recognition and therapeutic targeting. Neurofibrillary tangle maturity encompasses three levels: pretangles, mature tangles, and ghost tangles. In this review, we detail distinct and overlapping chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
179
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 167 publications
(189 citation statements)
references
References 199 publications
(569 reference statements)
10
179
0
Order By: Relevance
“…Ghost tangles are the remnants of mature tangles once the neurons have died and are recognized by faintly stained bundles of fibers with no associated nucleus [1,2,49]. Additionally, intermediaries exist between these three neurofibrillary tangle maturity levels [42]. The first intermediary, between pretangles and mature tangles, has intensely stained tau accumulation in the neuron, but lacks the fullness of the mature tangle.…”
Section: Introductionmentioning
confidence: 99%
“…Ghost tangles are the remnants of mature tangles once the neurons have died and are recognized by faintly stained bundles of fibers with no associated nucleus [1,2,49]. Additionally, intermediaries exist between these three neurofibrillary tangle maturity levels [42]. The first intermediary, between pretangles and mature tangles, has intensely stained tau accumulation in the neuron, but lacks the fullness of the mature tangle.…”
Section: Introductionmentioning
confidence: 99%
“…TBDThe table represents the recent approaches to tau therapeutics highlighting the focus on mechanisms based primarily from preclinical models AD Alzheimer disease, CBS corticobasal syndrome, PSP progressive supranuclear palsy a Proposed potential as a prevention therapy is based on how likely the known mechanism of action aligns with the earliest stages of tau-pathology (soluble extracellular tau, reversibility of initial aggregated pathology), the known side effect profile (long term treatments likely required) and the available data on clinical efficacy b Estimated enrollment stage AD (e.g. post-mortem studies) there is a limited understanding of how changes in soluble tau predict or are related to the evolution of aggregated tau[91]. However, the DIAN study indicates that p-tau increases approximately 20 years before tau PET increases[59].…”
mentioning
confidence: 99%
“…Tau aggregates exhibit cell–cell transfer, which leads to seeding and further aggregation, supporting the concept of region to region spreading of phosphorylated tau in AD [ 97 ]. These plaques and NFTs are primarily deposited in brain regions, such as the hippocampus, amygdala, entorhinal cortex, and basal forebrain, which reportedly play an essential role in memory, learning, and emotional behaviors; plaques and NFTs reduce the number of synapses in these areas [ 55 , 98 , 99 ]. It has been suggested that an imbalance between kinases and phosphatases leads to aberrant tau hyperphosphorylation.…”
Section: Linking Os and Proteinopathy In Admentioning
confidence: 99%